THE VEDIC LEARNING TRADITION IN THE NUSANTARA AND ITS RELEVANCE TO THIS DAY - Si Luh Nyoman Seriadi (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2024)
Study This review about tradition Vedic learning spread across the archipelago and its relevance until day This . Tradition This covers practice teaching - centered learning ancient India, especially the Vedas, which have adopted and adapted with context culture local in the Indonesian archipelago. Method research used covers studies literature, interviews with experts , as well observation direct to practices still traditional endure . Research result show that tradition Vedic learning in the archipelago has deep roots in history culture and religion local. Practices This covers reading, interpretation, and practice texts sacred Vedas, as well teaching direct from teacher to student. In many community, tradition This guarded with carefully and preserved as part important from inheritance culture. Relevance tradition Vedic learning up to day This can seen from a number of aspect. First, values ethics , spirituality , and philosophy contained in Vedic teachings remain relevant in guide life and values modern society . Second , practices meditation , yoga, and originating worship from Vedic teachings have recognized benefits in a way wide for well-being physical and mental. Third, as part from inheritance culture , tradition Vedic learning provides identity and pride for the community that inherits and practices it . Although Thus, tradition Vedic learning in the archipelago is also facing problems challenge . Globalization , modernization and change social has threaten continuity practices This. However , efforts preservation and revitalization currently carried out by various party For guard continuity tradition this is in the middle dynamics of the times. In context formal education, tradition Vedic learning also provides inspiration for development curriculum religious education or an inclusive and based philosophy universal values. With Thus, research This give contribution in understanding about inheritance Rich culture and relevance values ancient in modern-day context